Análise da dinâmica do uso e ocupação da terra em pequenos municípios baianos do semi-árido brasileiro: o caso de Teofilândia - José Luiz Oliveira Batista; Rosangela Leal Santos (Revista de Geografía Norte Grande)
In order the socioeconomic dynamics of the semi-arid region, the temporal-spatial evolution characteristics this region were evaluated. A small city (approximately 21,000 inhabitants) with an average profile on the social and economic aspects of the semi-arid region was chosen in order to analyse the changes in the land use and occupation over a period of 15 years (1993 to 2008). Remote sensing techniques were used to go along by digital image processing of Landsat 5 TM. Images from subsequent periods were used to capture the seasonal contrast between dry and wet periods due to the high contrast presented by the landscape, especially in relation to biomass concentration in these two distinct periods. Five main classes of land use e land cover were defined: pasture, bare soil, Caatinga, urban area and water. Results finally proved the extensive use of land through the practice of extensive farming.